The Improvement of Energy Harvesting Efficiency of Constant Current Source - Martynyuk V.V.; Kosenkov V.D.; Fedula M.V. (Problems of the Regional Energetics)
This study aims at determination the maximum power point parameters for the constant current source with nonlinear parasitic elements. The aim has been achieved by analyzing the differential resistance and equivalent parameters of a circuit with a constant current source. As a result, the buck-boost converter circuit is considered with the equivalent current source, which is formed with a photovoltaic module. The problem of the maximum photovoltaic module of energy harvesting is related to the research of its nonlinearity, which determines operating points at the current-voltage curves under different irradiances and temperatures. Thus, the differential resistance of photovoltaic module is examined to determine the parameters of the maximum power point mode. The main result of the research is the model, which differs from the known models by the description of the dependence between the buck-boost converter duty cycle and input equivalent current source parameters in the maximum power point mode. The results of modelling are supported by experimental research of the laboratory layout. The presented circuit ensures the operating point close to the maximum power point of the solar panel equivalent current source. The duty cycle of the buck-boost converter is determined directly from the equivalent current source model with the parameters estimated analytically from the irradiance and temperature of the solar cells. The presented approach allows developing the maximum power point tracking algorithms based on the estimation of the equivalent current source parameters that provide improvement of the energy harvesting efficiency.